Effect of temperature on yellow leaf disease symptoms and its associated areca palm velarivirus 1 titer in areca palm (Areca catechu L.) - Khan, Latif Ullah; Cao, Xianmei; Zhao, Ruibai; Tan, Hang; Xing, Zengyu; Huang, Xi (Frontiers in Plant Science, 2022)
Yellow leaf disease (YLD) has been a major limiting factor threatening areca palm commonly known as betel palm (Areca catechu L.) plantations in Hainan, China. The YLD disease is closely associated with areca palm velarivirus 1 (APV1), which belongs to the family Closteroviridae. YLD-affected betel palms show more serious yellowing symptoms in winter than in summer based on anecdotal observations. In the present work, the underlying mechanism was investigated. We first observed that the severity of YLD symptoms was closely related with the APV1 viral titer determined by qRT-PCR and ELISA under natural conditions. To further investigate whether temperature plays a key role in APV1 accumulation, the areca palm seedlings were artificially inoculated with APV1-positive mealybugs (Ferrisia virgata) and then cultivated under controlled conditions. According to our results, the YLD symptoms severity in inoculated seedlings were closely associated with temperature, e.g., severest symptoms at low temperature (16/22 ± 2°C, night/day), severer symptoms at room temperature (24/26 ± 2°C, night/day), while moderate symptoms at high temperature (27/34 ± 2°C, night/day). The qRT-PCR and ELISA results showed that APV1 titer accumulates significantly abundant at low temperature as compared to high and room temperatures. In conclusion, this is the first report about the temperature effects on the symptoms severity of YLD and APV1 titer, which may have important implications for the epidemiology of YLD.